STUDI EKSPERIMEN KEKUATAN TEKAN MORTAR DENGAN CAMPURAN KAPUR, BUBUKAN BATA MERAH DAN PASIR - Jepira, Harry Janto; Chandra, Jimmy; Bhara, Firnimus Konstatinus (Jurnal Teknik Sipil dan Arsitektur, 2025)
This study aims to evaluate the use of lime as an alternative binder to replace cement in mortar mixtures, with the addition of crushed brick powder to enhance mechanical strength. This approach offers an environmentally friendly solution to the high carbon emissions associated with cement production. The mortar mixture was prepared using a ratio of 1:1:3 (lime : crushed brick powder : sand) with a water-to-binder ratio of 0.5. Tests were conducted to assess the compressive strength and density of the mortar at 7, 14, and 28 days of curing. The results showed that the average compressive strength increased with curing time, reaching 1.49 MPa at 7 days, 1.86 MPa at 14 days, and 2.40 MPa at 28 days. The mortar density ranged from 2,080 to 2,680 kg/m³, with average values of 2,513 kg/m³ (7 days), 2,342 kg/m³ (14 days), and 2,230 kg/m³ (28 days). These findings indicate that the combination of lime and crushed brick powder improves mortar performance and has the potential to be a more sustainable alternative construction material. Keywords: Mortar, Lime, Crushed brick powder, Compressive strength, Density